2015
DOI: 10.1016/j.jbusres.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Optimal content for warning messages to enhance consumer decision making and reduce problem gambling

Abstract: Warning messages for electronic gaming machines (EGMs) have been mandated to increase consumers' ability to make informed rational decisions and reduce excessive gambling consumption. However existing warnings have limited effectiveness. This paper presents the results of the first in situ trial of dynamic warnings for EGMs to evaluate the impact of message content. A series of dynamic warning messages was displayed across EGMs in venues. Gamblers (N=667) completed surveys to assess message recall and impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 56 publications
3
35
1
Order By: Relevance
“…Theory advancement in the context of problem gambling is important because, just as with “common advertising,” people with social problems need to be aware of products and services that would benefit them (Calderwood & Wellington, ). Interest in the potentially harmful forms of consumption such as smoking, drinking, and gambling has begun to receive greater attention in recent years, especially among social marketing, public health, and public interest groups (Gainsbury, Aro, Ball, Christian, & Russell, ; Hendriks, van den Putte, & de Bruijn, ; Lewis et al., ; Sato, Drennan, & Lings, ). However, the use of emotionally stimulating message content designed to facilitate responsible gambling and/or prompt at‐risk gamblers to seek help has received limited academic attention (Harris, Parke, & Griffiths, ), despite the theoretical and empirical accounts highlighting the important role that emotion plays in the decision‐making process (Lerner, Li, Valdesolo, & Kassam, ).…”
Section: Discussionmentioning
confidence: 99%
“…Theory advancement in the context of problem gambling is important because, just as with “common advertising,” people with social problems need to be aware of products and services that would benefit them (Calderwood & Wellington, ). Interest in the potentially harmful forms of consumption such as smoking, drinking, and gambling has begun to receive greater attention in recent years, especially among social marketing, public health, and public interest groups (Gainsbury, Aro, Ball, Christian, & Russell, ; Hendriks, van den Putte, & de Bruijn, ; Lewis et al., ; Sato, Drennan, & Lings, ). However, the use of emotionally stimulating message content designed to facilitate responsible gambling and/or prompt at‐risk gamblers to seek help has received limited academic attention (Harris, Parke, & Griffiths, ), despite the theoretical and empirical accounts highlighting the important role that emotion plays in the decision‐making process (Lerner, Li, Valdesolo, & Kassam, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the Reno-model – a framework for the design and implementation of RG tools - warn of the potential harms that RG tools could cause to non-problem gamblers and encourage stakeholders to be aware of them ( Blaszczynski et al, 2004 ; Ladouceur, Blaszczynski, Shaffer, & Fong, 2016 ). Although not disturbing recreational gamblers by RG tools has been described as preferable by other researchers ( Auer, Littler, & Griffiths, 2015 ; Gainsbury, Aro, Ball, Tobar, & Russell, 2015 ; Monaghan, 2008 , Monaghan, 2009 ), there is little empirical evidence to suggest that RG tools do in fact inconvenience non-problem gamblers and make them more likely to abandon gambling services with extensive consumer protection programs.…”
Section: Introductionmentioning
confidence: 94%
“…The results of a survey of 10,838 online gamblers from 96 different countries suggest that implementation of RG tools can enhance consumers' favorable attitudes towards a gambling operator ( Gainsbury et al, 2013 ), which contradicts the notion of gamblers' being prone to abandon a gambling provider due to the presence of RG tools. Only a small fraction of gamblers in earlier studies indicated that they have been disturbed by RG tools ( Gainsbury et al, 2015 ; Monaghan, 2008 ; Monaghan & Blaszczynski, 2010 ) and little is known about the relationship between degree of gambling problems and attitudes towards RG. A study conducted with Swedish customers showed that the most common source of frustration was the need to restrict their gambling activity; this is an expected adverse effect of RG tools because gambling responsibly implies being able to set limits on one's gambling ( Griffiths, Wood, & Parke, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic messages that break any dissociation and attract attention have been more effective when they ask gamblers "Do you need to take a break? ", as opposed to providing factual information about the low chances of winning with no suggested behavioural action (Gainsbury, Aro, Ball, Tobar, & Russell, 2015b). One of the most effective policy changes in terms of reducing gambling expenditure was the introduction of smoking bans that caused gamblers to take a break and leave the gambling venue to smoke, resulting in a reduction in gambling among smokers (Bradley & Becker, 2011;Garrett & Pakko, 2010;Pakko, 2008).…”
Section: Applying Behavioural Economic Principles To Gamblingmentioning
confidence: 99%